To compare the efficacy of fortification of expressed breast milk with medium chain triglycerides and coconut oil on the physical growth of very low birth weight babies - Dr. Swati Joshi; Dr. Nilesh Jain (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: The most important factor leading to growth failure in VLBW babies is inadequate nutrition. Though, higher amounts of protein, sodium, chloride, and magnesium are available in preterm human milk than those found in term milk, these levels still remain below recommendations. To compensate these requirements, human milk for preterm infants is routinely fortified to increase energy, protein and mineral intake. In the past, very few studies have been done to find out the efficacy of medium chain triglycerides and coconut oil for fortification of human milk. Since, a major chunk of LBW babies exists in our country, this study is undertaken.Objectives: To study and compare the physical growth (weight, length and head circumference) over a period of two months in each study group.Design: Prospective cohort study.Setting: The study was conducted from April, 2015 to August, 2016 at Department of Pediatrics, MY hospital and CNBC, Indore.Participants: 225 VLBW babies (<1.5 kg) admitted in SCNU and postnatal wards.Intervention: The babies were assigned to group 1, 2 and 3 in serial order. Sample size in each group was 75.Group1- Given expressed breast milk with lactodex-HMF.Group 2- Given expressed breast milk with lactodex- HMF and MCT (Simyl MCT oil).Group 3- Given expressed breast milk with lactodex- HMF and coconut oil (Parachute-100% edible oil) Physical growth was monitored every week for 2 months.Results: Significant physical growth (weight, length and head circumference) was noticed in each of the study groups over 2 months (p value<0.05). There was no statistically significant difference in the physical growth between the groups (p>0.05).Conclusion: There is no advantage of MCT or coconut oil in addition to Lactodex- HMF on the physical growth of VLBW babies.